White matter degeneration profile in the cognitive cortico‐subcortical tracts in Parkinson's disease. Issue 7 (23rd April 2018) - Hanganu, Alexandru; Houde, Jean‐Christophe; Fonov, Vladimir S.; Degroot, Clotilde; Mejia‐Constain, Beatriz; Lafontaine, Anne‐Louise; Soland, Valérie; Chouinard, Sylvain; Collins, Louis D.; Descoteaux, Maxime; Monchi, Oury
Abstract: Background: In Parkinson's disease cognitive impairment is an early nonmotor feature, but it is still unclear why some patients are able to maintain their cognitive performance at normal levels, as quantified by neuropsychological tests, whereas others cannot. The objectives of this study were to perform a cross‐sectional study and analyze the white matter changes in the cognitive and motor bundles in patients with Parkinson's disease. Methods : Sixteen Parkinson's disease patients with normal cognitive performance, 19 with mild cognitive impairment (based on their performance of 1.5 standard deviations below the healthy population mean), and 16 healthy controls were compared with respect to their tractography patterns between the cortical cognitive / motor regions and subcortical structures, using high angular resolution diffusion imaging and constrained spherical deconvolution computation. Results : Motor bundles showed decreased apparent fiber density in both PD groups, associated with a significant increase in diffusivity metrics, number of reconstructed streamlines, and track volumes, compared with healthy controls. By contrast, in the cognitive bundles, decreased fiber density in both Parkinson's groups was compounded by the absence of changes in diffusivity in patients with normal cognition, whereas patients with cognitive impairment had increased diffusivity metrics, lower numbers of reconstructed streamlines, and lower track volumes. Conclusions : Both PD groups showed similar patterns of white matter neurodegeneration in the motor bundles, whereas cognitive bundles showed a distinct pattern: Parkinson's patients with normal cognition had white matter diffusivity metrics similar to healthy controls, whereas in patients with cognitive impairment white matter showed a neurodegeneration pattern. © 2018 International Parkinson and Movement Disorder Society